ANALISIS PENGARUH PEMBERDAYAAN DAN GAYA KEPEMIMPINAN TERHADAP PENINGKATAN SELF EFFICACY DALAM RANGKA PENCAPAIAN KOMITMEN ORGANISASI (Studi Empiris pada Kantor Pelayanan Pajak di Semarang) - Yuliani Purwaningrum; Pahlawansyah Harahap (Universitas Semarang, 2014)
This study attempts to examine the effect of empowerment and leadership style to increase self efficacy in achieving the organization's commitment to the tax office in Semarang. The problem in this study due to lack of involve employees in decision making, lack of facilities in accommodating the desireto be empowered from the staff and leadership style that is still far from perfect. This research used purposive random sampling method and data used in this research is in the form of a questionnaire. The study population numbered 409 employees in the executive level, while this sample of 110 employees of the tax office in Semarang. Literature review of relevant literature has been developed for resulting in a hypothetical model consists of 5 observations and 22 variables were tested using Structural Equation Model (SEM) with the criteria of goodness of fit and hypothesis testing are done with AMOS. Based on the results of confirmatory analysis, has found the absence of differences between the sample covariance matrix and covariance matrix dietimasi population and 22 variables significant observation is the dimension of the latent variable. From SEM analysis, full model, generate all the goodness of fit criteria can be met. All the hypotheses can be accepted and significant with significance level of 5%. Thus, empowerment and leadership style variables can affect the increase in self efficacy and organizational commitment